Kinetics and mechanism of ultrasonic enhanced separation of zinc from tannin germanium residue - Haokai Di; Ming Liang; Kun Yang; Libo Zhang (Journal of Saudi Chemical Society, 2024)
Tannin germanium residue (TGR) is the main enrichment in the process of hydrometallurgical extraction of germanium (Ge). The removal effect of impurity zinc (Zn) from TGR greatly affects the purity of TGR and the subsequent production process. In this study, a new method of high efficiency separation of impurity Zn from TGR by ultrasonic intensification was proposed. The results of single factor experiment showed that under the optimal purification conditions of ultrasonic frequency of 20 kHz, ultrasonic power of 225 W, acid concentration of 20 g/L, liquid–solid ratio of 7.5:1, reaction temperature of 40 °C and reaction time of 30 min, the removal efficiency of impurity Zn from TGR was 88.57 %, which is 5.22 % higher than the conventional purification method. The kinetic analysis based on the shrinking core model indicated that the removal of impurity Zn in TGR was controlled by the diffusion step, and the apparent activation energy of the reaction was reduced by the introduction of ultrasonic. The microscopic mechanism of ultrasonic action showed that the ultrasonic increased the surface free energy of solids and improved the wettability of the purified reagent to solids. When the ultrasonic power was 225 W, the ultrasonic can not only destroy the impurity inclusions and break the solid reactants into small particles, but also avoid the secondary agglomeration of small particles.